Seismic evidence for a plume-modified oceanic lithosphere–asthenosphere system beneath Cape Verde - Liu, Xin; Zhao, Dapeng (Geophysical journal international, 2021)
SUMMARY We determine a new 3-D shear wave velocity (Vs) model down to 400 km depth beneath the Cape Verde hotspot that is far from plate boundaries. This Vs model is obtained by using a new method of jointly inverting P- and S-wave receiver functions, Rayleigh-wave phase-velocity data and S-wave arrival times of teleseismic events. Two Vs discontinuities at ∼15 and ∼60 km depths are revealed beneath volcanic islands, which are interpreted as the Moho discontinuity and the Gutenberg (G) discontinuity. Between the north and south islands, obvious high-Vs anomalies exist in the uppermost mantle down to a depth of ∼100–150 km beneath the Atlantic Ocean, whereas obvious low-Vs anomalies exist in the uppermost mantle beneath the volcanic islands including the active Fogo volcano. These low-Vs anomalies merge into a significant column-like low-Vs zone at depths of ∼150–400 km beneath the Cape Verde swell. We propose that these features in the upper mantle reflect a plume-modified oceanic lithosphere–asthenosphere system beneath the Cape Verde hotspot.